Case report: Leptospirosis with multi-organ failure complicated by massive upper gastrointestinal bleeding in a non-epidemic setting with successful management - Thalji, Mariam; Qunibi, Hanan; Muhtasib, Loai; Hroob, Hasan; Al-Zughayyar, Ashraf; Salhab, Rafiq; Abu Asbeh, Yousef (Frontiers in Surgery, 2023)
Leptospirosis is a common zoonotic disease with a wide range of clinical manifestations, specifically in tropical regions. Weil's disease is considered a severe form of leptospirosis seen in a minority of leptospirosis cases with considerable mortality. These patients typically developed the triad of jaundice, acute renal injury, and hemorrhages. Herein, we reported a case of a 28-year-old male transferred to our intensive care unit due to severe leptospirosis with diffuse alveolar hemorrhage, acute respiratory distress, cholestatic jaundice, and renal injury. The patient was successfully managed with appropriate antimicrobial treatment and other supportive measures, including mechanical ventilation, vasopressor, and corticosteroid therapy. Ten days after admission, the patient unexpectedly developed uncontrollable massive upper gastrointestinal bleeding, requiring immediate surgical interventions. Splenectomy, partial gastrectomy, along with gastro-esophageal anastomosis were performed. Following a prolonged hospitalization, the patient fully recovered and was discharged home with excellent clinical outcomes. This fulminant leptospirosis case described here should assist in informing medical professionals of the clinical significance of this serious, occasionally fatal illness. Moreover, leptospirosis should be considered in any location wherever risk factors are present, not just in epidemic and tropical areas. In this case, we pointed out that serious complications of leptospirosis, such as hemorrhage, may happen despite their rarity. In such cases, adopting an integrated multidisciplinary team approach is essential to prevent complications and reduce mortality